ANALYSIS OF THE INFLUENCE OF TRANSACTIONAL LEADERSHIP STYLE, COMPETENCE, AND JOB SATISFACTION ON THE PERFORMANCE OF SALES DIVISION EMPLOYEES IN A GOVERNMENT BANK - Sjahril, Savira Alifa; Barry, Rinto Rain (FEB Universitas Sam Ratulangi Manado, 2024)
Human resource management plays a crucial role in a company's success by ensuring productive employee performance. This research aims to analyze the influence of transactional leadership style, employee competence, and job satisfaction on the performance of the Sales Division employees at a government bank. A quantitative method with a causal research design was used in this study. Data were collected through a questionnaire from 163 respondents and analyzed using reliability analysis, validity analysis, and Structural Equation Modeling (SEM). The results showed that transactional leadership style, employee competence, and job satisfaction have a positive and significant influence on employee performance. The managerial implications of this research highlight the need for companies to improve employee performance through the development of transactional leadership styles, enhancing competencies, and increasing job satisfaction. Further research is suggested to consider adding new variables that may affect employee performance.